Comparison of Intranasal Midazolam and Rectal Diazepam as Anticonvulsant in Children - Gunawan, Prastiya Indra; Rulian, Fadil; Saharso, Darto (Journal of Nepal Paediatric Society, 2016)
Introduction: Rectal diazepam is reputed as the gold-standard management of childhood seizures. Otherwise, intranasal (IN) midazolam has no first-pass metabolism and faster onset of action. The effectiveness and easier route of these drugs are important choices for faster seizure cessation. The aim of this study was to clarify the effectiveness of intranasal midazolam compared with rectal diazepam for seizure termination. Material and Methods: The children, one month until 18 years of age, presented with acute seizures. Patients were randomly classified into two groups with either received intranasal midazolam or rectal diazepam for seizure termination. Interval time of drug administration to cease seizure was compared. The log-rank analysis was used for statistical analysis. Side effect of both drugs were evaluated. Results: There were 60 patients enrolled the study, 30 in each group. The median time interval for seizures cessation with intranasal midazolam was 42 seconds, otherwise in rectal diazepam group was 180 seconds. There was statistically significant difference interval time between two groups (p<0.01). None of the both groups had any significant side effects statistically. Conclusion: Intranasal midazolam is effective to terminate a seizure in children. It can be used as an alternative treatment for seizures in patients with intravenous or rectal route difficulties. J Nepal Paediatr Soc 2015;35(2):117-122